2023
DOI: 10.1039/d3mh00485f
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl-C60 liquid electrets as deformable mechanoelectric generators

Abstract: Special attention is being paid to the potential applicability of various soft electronics in deformable/wearable devices. These devices must be constantly connected to energy sources to ensure their uninterrupted operation....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Alkylπ FMLs have an electroactive π-moiety wrapped with insulating alkyl chains, making them suitable for storing electrostatic charges inside the liquid and functioning as liquid electrets. [18][19][20] This study revealed that gelation improves electret performance and eliminates the need for supporting materials in MEG devices.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…Alkylπ FMLs have an electroactive π-moiety wrapped with insulating alkyl chains, making them suitable for storing electrostatic charges inside the liquid and functioning as liquid electrets. [18][19][20] This study revealed that gelation improves electret performance and eliminates the need for supporting materials in MEG devices.…”
mentioning
confidence: 73%
“…Regarding the change in V oc over the course of days, the gel device maintained a higher V oc than the liquid one (Figure S31). When we utilize liquid materials for electrets, [18,20] we must impregnate them into the nonwoven supporting fabric to prevent short circuits due to contact between the electrodes (Figure S30b). In contrast, there is no contact between electrodes even without the supporting fabric in the case of gels with improved elasticity compared to liquids, and it showed a vibration power generation function of 64 � 5 % V oc compared to the device with supporting fabric (Figure 4f and Table S4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Solid state materials have conventionally been employed for electrets as an electric field needs to be fixed within the material. However, recent works have focused on creating soft electrets 5–13 to enable their use in wearable devices or as actuators. These materials can be achieved using soft polymers such as elastomers.…”
Section: Introductionmentioning
confidence: 99%